Implementasi Teknik Rotoscoping pada Pembuatan Film Animasi 3D Hang Tuah Ksatria Melayu - Muhammad Adha Fajri Jonison; Anggy Trisnadoli (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The development of information technology in the multimedia field is growing very rapidly today. Multimedia development is often found in making animated films. Animation is an image that moves and is arranged so that it makes inanimate objects appear to be moving. Animation initially has a problem, where it is difficult for an animator to create animation with complex movements to imagine directly and sometimes the results will look stiff. Max Fleischer also saw it as a problem, so he invented rotoscoping. Rotoscoping is a technique for making animation by tracing the movements of an actor. This technique is used to create movements that are complex to imagine directly so that the animation movement is realistic. In implementing rotoscoping techniques in an animated film, a folk tale entitled Hang Tuah Ksatria Melayu was adopted. This folktale will be packaged into a 3D animated film using rotoscoping techniques. With the creation of a 3D animated film, the folklore of Hang Tuah Ksatria Melayu, an animated film was created with realistic character movements and people get moral messages of Hang Tuah Ksatria Melayu.